2000
DOI: 10.1095/biolreprod62.6.1804
|View full text |Cite
|
Sign up to set email alerts
|

Horse Conceptuses Secrete Insulin-Like Growth Factor-Binding Protein 31

Abstract: Insulin-like growth factor-I (IGF-I) promotes early embryonic development in several species. In the rabbit, IGF-I binds to the embryonic coats from Day 3 of development onward by a 38-kDa protein that is probably insulin-like growth factor-binding protein 3 (IGFBP3). In the present study, ligand, Western, and Northern blot analyses were used to demonstrate the presence of IGF-I-binding activity, several immunoreactive IGFBP3 proteins, and IGFBP3 mRNA in horse conceptuses with particularly large amounts of imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…IGF1 is known to be present in the yolk sac fluid of the conceptus, in uterine flush fluid, and in the endometrium of mares between days 12 and 18 of pregnancy (Salute & Tucker 1992, Walters et al 2001) and the equine conceptus is known to bind IGFs at least from day 10 after ovulation (Herrler et al 2000). The equine conceptus also produces significant quantities of estrogen from day 12 (Flood et al 1979, Heap et al 1982, Raeside et al 2004).…”
Section: Embryogenesis After Asynchronous Embryo Transfermentioning
confidence: 99%
“…IGF1 is known to be present in the yolk sac fluid of the conceptus, in uterine flush fluid, and in the endometrium of mares between days 12 and 18 of pregnancy (Salute & Tucker 1992, Walters et al 2001) and the equine conceptus is known to bind IGFs at least from day 10 after ovulation (Herrler et al 2000). The equine conceptus also produces significant quantities of estrogen from day 12 (Flood et al 1979, Heap et al 1982, Raeside et al 2004).…”
Section: Embryogenesis After Asynchronous Embryo Transfermentioning
confidence: 99%
“…Immunodetection methods were used to show that horse embryos produce IGFBP3 by themselves and secrete it towards the maternal side, i.e. it is detectable within the coats [Herrler et al, 2000] (fig. 6).…”
Section: Embryonic Coats -A Mailbox Of Early Embryo-maternal Signallingmentioning
confidence: 99%
“…Recently it has been reported that HB-EGF significantly increases blastocyst formation of human embryos in in vitro culture Sargent et al, 1998]. The presence of HB-EGF in embryos of this stage might explain the extreme expansion seen in horse embryos from day 10 onwards (43.8 B 17.2 to 75.0 B 21.5 mm 3 within 4 h) [Herrler et al, 2000].…”
Section: Function Of Embryonic Coatsmentioning
confidence: 99%
“…Equine yolk-sac wall tissues before fixation express unusually large amounts of the GM2-activator protein (GM2AP) implicated in transport and catabolism of glycolipids (Quinn et al 2006). They also produce insulin-like growth factor-binding protein 3 that binds insulin-like growth factor which is important for embryonic development (Herrler et al 2000a). At the same time, a selectively permeable capsule composed largely of polysaccharides might shield embryonic antigens from immune rejection (Betteridge 1989) before non-classical major histocompatibility complex (MHC) class 1 expression and other immunoregulatory mechanisms prevent the rejection of paternal alloantigens in the invading trophoblast (Hunt et al 2005, Trowsdale & Betz 2006.…”
Section: Introductionmentioning
confidence: 99%